A morada do artista - Oliveira Neto, Mario Cysneiros de (2018)
In this dissertation we have realized a reflective study over some of the reasons for the existence of the creative impulse and of Art. We had as a general goal to investigate the motivations for production and appreciation of art through theories of psychanalyses, philosophy and immersion in the artistic universe of Francisco Brennand. From psychanalyses, we’ve studied the concepts of pulsion, phantasy and sublimation in Sigmund Freud, the bond between sexuality and regression to the motherly womb in Sándor Ferenczi and the theory of creativity of Donald Woods Winnicott. From philosophy, we’ve used the concept of will from Arthur Schopenhauer, the subjective experience of spaces in the theory of Gaston Bachelard and the transcendence phenomena under the prism of Plato. Concerning the field research, we’ve investigated the creative aspects of Francisco Brennand and his relations with his atelier through personal contact and an interview with the artist, visits to the Oficina Brennand and access to the artistic and bibliographical collection of the place, as well as through texts and videos published in the media. Having collected the data, we’ve stablished connections between his artistic production with the theories studied and we’ve developed some thought and intuitions. We’ve oriented the research from dimensions, three spaces, the intrapsychic, intersubjective and transcendence, and to facilitate the understanding of our purpose we’ve created a metaphorical image, The Tree of Existence, which, respecting this tripartition, organizes our theoretical writings and offers a general view of the existing dynamics between the dimensions. We’ve considered the presence of a feeling of existential discomfort due to the interaction between those dimensions, and the existence of a conflict of opposing forces, each plane seeking to impose itself over the other and be dominant. Then we followed the guiding hypothesis that through the fruition of art, its creation and contemplation, there would be a reduction in the feeling of discomfort, and that this decrease would happen through two main experiences, two phenomena, the existential increase due to the achievement of metaphysical planes and the movement of return to a mythical past of fusion and completeness – the fire. This fact showed resemblances between the path and destiny of sexuality and art, sex and the divine, chaos and the superior world. The present text sought to explore some of these purposes and their means of realization.